Adjunctive use of hepatic angioembolization following hemorrhage control laparotomy. Issue 5 (May 2020) - Matsushima, Kazuhide; Hogen, Rachel; Piccinini, Alice; Biswas, Subarna; Khor, Desmond; Delapena, Samantha; Strumwasser, Aaron; Inaba, Kenji; Demetriades, Demetrios
Abstract : BACKGROUND: Severe liver injuries pose a challenge to trauma surgeons. While the use of hepatic angioembolization (HAE) has been evaluated as a component of the nonoperative management of liver injury, little is known about the efficacy of postoperative HAE in patients who require hemorrhage control laparotomy (HCL) for liver injury. The purpose of this study is to evaluate the impact of HAE following HCL on patient survival. METHODS: This is a retrospective cohort study using the American College of Surgeons Trauma Quality Improvement Program database from January 2013 to December 2014. In propensity score matched (2:1) patients who underwent HCL-only or HCL + HAE, the impact of adjunctive use of HAE on patient survival was examined with the Cox proportional hazards regression analysis adjusting for transfusion requirement within 4 hours. We also performed a subgroup analysis in patients without severe traumatic brain injury (Abbreviated Injury Scale head ⩽3). RESULTS: A total of 1, 675 patients met our inclusion criteria. Of those, 75 (4.5%) patients underwent HAE after HCL (median hours to HAE, 5 hours after admission). In 225 propensity score-matched patients, the use of HAE following HCL was significantly associated with improved 24-hour mortality, but not in-hospital mortality. In the subgroup of patients without severe traumatic brain injury (n = 189), we observed significant survival benefits (24-hour and in-hospital mortality) associated with the adjunctive use of HAE. CONCLUSION: The results of our study suggest that the adjunctive use of HAE might improve survival of patients who require HCL for liver injury. Further prospective study to determine the indication for postoperative HAE is still warranted. LEVEL OF EVIDENCE: Therapeutic study, level III.